Escape Room Pedagogy and Its Role in Design Thinking Education. - Wszołek, Mariusz; Lewe, Thomas; Harman, Jon; Sikkes, Theo (International Journal of Art & Design Education, 2026)
This paper explores the use of Escape Room pedagogy as an innovative approach to teaching design methods such as design thinking in creative education. It compares various models and frameworks from the fields of design thinking, learning design and Escape Room design and identifies six common characteristics. It argues that Escape Rooms can provide an engaging, immersive and authentic learning experience that fosters problem‐solving, collaboration and critical thinking skills. The paper suggests that participating in Escape Rooms can assist students in bridging the practice‐theory gap, understanding the complexity of design problems and developing relevant skills and competencies. It calls for further research to test the hypothesis of the similarity between design thinking, educational Escape Rooms and learning design frameworks.